Effect of Work Stress and Work Conflicton Performance of Employees - Willy Cahyadi; Nursaimatussaddiya Nursaimatussaddiya; Lukieto Cahyadi (Jurnal Mantik, 2021)
This research was conducted at the Office of the Deputy Mayor of TebingTinggi City, which aims to determine how the influence of work stress and work conflict on employee performance at the office of the mayor of TebingTinggi. The results of hypothesis testing using multiple regression analysis with two independent variables and one dependent variable indicate that: The proposed H1 states that: Job stress affects employee performance at the TebingTinggi Mayor's Office, from table 4.11 it can be seen if the t-count value is 2.085 or greater than t-table (? : 5%, df : 76 = 1.665), besides that the significance value is 0.040 or less than the model significance value of 0.05. Then H1 is accepted, meaning that work stress has an effect on employee performance at the TebingTinggi Mayor's Office. The proposed H2 states that: Work Conflict affects Employee Performance at the TebingTinggi Mayor's Office, from table 4.11 it can be seen if the t-count value is 2.702 or greater than t-table (? : 5%, df : 76 = 1.665), In addition, the significance value is 0.009 or less than the model significance value of 0.05. Then H2 is accepted, meaning that Work Conflict affects Employee Performance at the TebingTinggi Mayor's Office. The proposed H3 states that work stress and work conflict simultaneously affect employee performance at the TebingTinggi Mayor's Office. From table 4.12, the calculated F value is 15,624 or greater than the table F value (? : 5%, df numerator : 2 df denominator : 75, F-table: 3.12), in addition to the significance value of 0.000 or less than the model's significance of 0.05, it can be concluded that if H3 is accepted, it means that work stress and work conflict simultaneously affect employee performance at the mayor's office. High cliff.